Semiotic Analysis of the Commodification of Islamic Teachings in Sharia Bank Advertisements in Indonesia - El Ghiffary, Lazuardi; Widana, Gusti Oka (Nyimak: Journal of Communication, 2023)
This research aims to analyze the semiotics of the commodification of Islamic teachings in Islamic bank advertising in Indonesia. The research focuses on using C. S. Pierce’s semiotics approach to analyzing and explaining three main aspects: the meaning of Islamic signs in bank advertisements, the commodification of Islamic teachings, and the pattern of commodification of Islamic teachings in advertisements of BCA Syariah, Bank Mega Syariah, BSI, and BTPN Syariah. The research method employed is qualitative research that involves three key informants and three main informants. The data collected is analyzed using triangulated data interpretation to get a deeper sense. His findings  from that research revealed several important points. First, it is clear that the meaning of Islamic signs in Islamic bank advertisements in Indonesia does not clearly depict any Islamic symbols. This raises questions about the authenticity of that commitment of the Islamic bank with Islamic principles in its advertisements. Second, the semiotic analysis shows that the message structure, format, content, and source of the Islamic bank advertisements in Indonesia are inconsistent incorporating signs or symbols that represent Islamic teachings. This suggests that this advertising focuses again on business and marketing aspects more precisely than conveying Islamic values to the public. Third, it identified a pattern of commodification in this study not directly related to Islamic teachings but rather connected to its enhanced dual role of employees in Islamic banking. This suggests that in the process of commodification, factors e.g., labor became again dominant rather than religious values it should be the main focus of the Islamic bank. This research provides a deeper understanding than that of the commodification of Islamic teachings in Islamic bank advertising in Indonesia. These findings could serve as a basis for critiquing the marketing practices of Islamic banks and reconsidering the application of Islamic values in their marketing strategies.Keywords: C.S. Pierce semiotics, commodification of Islamic teachings, advertising for Islamic banks ABSTRAKPenelitian ini bertujuan untuk menganalisis semiotika mengenai komodifikasi ajaran Islam pada iklan bank syariah di Indonesia. Fokus penelitian menggunakan pendekatan semiotika CS Pierce untuk menganalisis dan menjelaskan tiga aspek utama, yaitu makna tanda syariah pada iklan bank, komodifikasi ajaran Islam, dan pola komodifikasi ajaran Islam pada iklan BCA Syariah, Bank Mega Syariah, BSI, dan BTPN Syariah. Metode penelitian yang digunakan ialah penelitian kualitatif dengan melibatkan tiga informan kunci dan tiga informan utama. Data yang dikumpulkan dijelaskan menggunakan interpretasi data triangulasi untuk mendapatkan pemahaman lebih mendalam. Hasil penelitian menunjukkan beberapa temuan penting. Pertama, pemaknaan tanda syariah pada iklan bank syariah di Indonesia terbukti tidak ada tanda syariah yang ditampilkan dengan jelas. Hal ini menimbulkan pertanyaan mengenai keaslian komitmen bank-bank syariah terhadap prinsip-prinsip Islam dalam iklan mereka. Kedua, analisis semiotika menunjukkan bahwa struktur pesan, format pesan, isi pesan, dan sumber pesan pada iklan bank syariah di Indonesia tidak memuat tanda atau simbol yang secara konsisten menggambarkan ajaran Islam. Hal ini mengindikasikan bahwa iklan-iklan tersebut lebih fokus pada aspek bisnis dan pemasaran daripada menyampaikan nilai-nilai Islam pada masyarakat. Ketiga, pola komodifikasi yang ditemukan dalam penelitian ini bukan terkait dengan ajaran Islam, melainkan terkait dengan peningkatan peran ganda karyawan perbankan syariah. Hal ini menunjukkan bahwa dalam proses komodifikasi, faktor-faktor seperti tenaga kerja menjadi lebih dominan daripada nilai-nilai agama yang seharusnya menjadi fokus utama bank syariah. Penelitian ini memberikan pemahaman yang lebih mendalam tentang komodifikasi ajaran Islam pada iklan bank syariah di Indonesia. Temuan-temuan ini dapat menjadi dasar untuk mengkritisi praktik pemasaran bank syariah dan mempertimbangkan ulang penerapan nilai-nilai Islam dalam strategi pemasaran mereka.Kata Kunci: Semiotika C.S. Pierce, komodifikasi ajaran Islam, Iklan bank syariah